The sustainability revolution: A societal paradigm shift - ethos, innovation, government transformation (Sociologisk Forskning, 2011)
The Sustainability revolution: A societal paradigm shift – ethos, innovation, governance transformationThis paper identifies several key mechanisms that underlie major paradigm shifts. After identifying four such mechanisms, the article focuses on one type of transformation which has a prominent place in the sustainability revolution that the article argues is now taking place. The transformation is piecemeal, incremental, diffuse – in earlier writings referred to as ”organic”. This is a more encompassing notion than grassroots, since the innovation and transformation processes may be launched and developed at multiple levels through diverse mechanisms of discovery and development. Major features of the sustainability revolution are identified and comparisons made to the industrial revolution.